EFFECT OF TILLAGE PRACTICES AND NUTRIENT MANAGEMENT ON FODDER YIELD OF OAT, SOIL FERTILITY AND MICROBIAL POPULATION - SAHAJA DEVA (The Bioscan, 2015)
A field experiment was carried out during rabi 2011-12 to study the effect of tillage (zero tillage, minimal tillage and conventional tillage) and nutrient management (75 per cent RDF, 75 per cent RDF + biofertilizers (Azotobacter + PSB), 100 per cent RDF, 100per cent RDF + biofertilizers(Azotobacter + PSB) practices on fodder yield and quality of oat. Conventional tillage recorded maximum green fodder yield with 342.23 q ha-1, dry fodder yield with 79.42 q ha-1 and maximum nutrient content with 238.22 kg N ha-1, 20.30 kg P2O5 ha-1 and 295.19 kg K2O ha- 1 and organic carbon content 0.60 kg ha-1 and maximum bacteria with 2.37 x 106, fungi 1.86 x 104 and actinomycetes 1.07 x 105 after harvest of crop. Application of 100% RDF along with Bio-fertilizers like Azotobacter and PSB recorded maximum green fodder yield with 329.76 q ha-1, dry fodder yield with 77.57 q ha-1 and maximum nutrient content with 236.30 kg N ha-1, 19.96 kg P2O5 ha-1 and 292.60 kg K2O ha-1 and organic carbon content 0.60 kg ha-1 and maximum bacteria with 2.50 x 106, fungi 1.92 x 104 and actinomycetes 1.10 x 105after after harvest of crop.